Using Relational Dialectic Theory in the tradition of gift-giving in the Indonesian Education environment - Arsyah Putra , Rizky Ramadhani; Utari, Prahastiwi; Sudarmo, Sudarmo (Journal of Social Interactions and Humanities, 2024)
Education, which is one of the "media" in the eradication of anti-corruption, still has an important role to play. However, the role of education in supporting anti-corruption prevention has reached a saturation point in society because the government's seriousness in carrying out strategic steps to prevent corruption crimes still seems slow. The research method uses descriptive analysis with a literature study approach. The theory of relational dialectic by L.A Baxter became an analytical instrument, to show the dynamics of giving gifts by students to educators as a form of gratuity that cannot be justified. The results of the study showed that there was a conflict between the two groups which was divided into satisfaction vs decision, cost vs reciprocity, and tradition vs code of ethics. The conclusion of this study is to show the dynamics of gratuities, which are carried out by both parties greatly affect the attitude of integration and honesty in the future. For this reason, there needs to be a role for the KPK institution in building an example of educators so that they can show the giving of gifts as a form of gratuity and a real violation of the law. The study of dialectical relational communication can certainly be considered for further research as a form of attention to anti-corruption attitudes in the educational environment as early as possible.